Bone Marrow Examinations: Findings from Four Year Retrospective Single Centre Review - Rahman, M Mizanur; Khan, MA; Afrose, Salma; Ara, Tasmin; Islam, Sirajul; Biswas, Akhil Ranjan (Journal of Medicine, 2010)
Background: Bone marrow examination is used for diagnosis of both haematological and non-haematological diseases. Materials and methods: In this retrospective study data from the registry of department of haematolgoy, Dhaka medical college was analyzed. Total 2340 bone marrow was reported for the period of 2006-2009. Results: The most prevalent disease is acute leukaemia (1022, 43.67%) followed by non-specific reactive and normal marrow (495, 21.15%). Conclusion: The study indicates that the indication for bone marrow is not optimum which is related with patient’s poor economic condition and physicians’ limited exposure to haematology. Sole reliability on Rowmanwsky stain is the major limitations of the bone marrow reports. Optimization of indication, reporting and further supplementary investigation is needed for further improvement. Keywords: Bone Marrow Examination; Laboratory Techniques and Procedures; Bangladesh DOI: 10.3329/jom.v11i2.5451 J MEDICINE 2010; 11 : 115-118